Atomic Force Microscopy for Biologists. - Morris, Victor J. (World Scientific Publishing Company, 2009)
Atomic force microscopy (AFM) is part of a range of emerging microscopic methods for biologists which offer the magnification range of both the light and electron microscope, but allow imaging under the ""natural"" conditions usually associated with the light microscope. To biologists, AFM offers the prospect of high resolution images of biological material, images of molecules and their interactions even under physiological conditions, and the study of molecular processes in living systems. This book provides a realistic appreciation of the advantages and limitations of the technique and the.